2000
DOI: 10.1097/00005768-200009001-00002
|View full text |Cite
|
Sign up to set email alerts
|

Validity of accelerometry for the assessment of moderate intensity physical activity in the field

Abstract: The count versus METs relationship for accelerometry was found to be dependent on the type of activity performed, which may be due to the inability of accelerometers to detect increased energy cost from upper body movement, load carriage, or changes in surface or terrain. This may introduce error in attempts to use accelerometry to assess point estimates of physical activity energy expenditure in free-living situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
537
7
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(585 citation statements)
references
References 18 publications
28
537
7
13
Order By: Relevance
“…No women fell within the moderate-intensity activity category on any occasion using the cut points of X574 (Swartz et al, 2000) and X1952 (Freedson et al 1998). Only the lower cut point of X191 (Hendelman et al, 2000) identified individuals with activity of moderate intensity or above. Table 5 shows the Pearson correlation coefficients for each assessment when activity was subdivided into low and moderate-high categories using the Hendelman cut-point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No women fell within the moderate-intensity activity category on any occasion using the cut points of X574 (Swartz et al, 2000) and X1952 (Freedson et al 1998). Only the lower cut point of X191 (Hendelman et al, 2000) identified individuals with activity of moderate intensity or above. Table 5 shows the Pearson correlation coefficients for each assessment when activity was subdivided into low and moderate-high categories using the Hendelman cut-point.…”
Section: Resultsmentioning
confidence: 99%
“…Compliance with the accelerometers was encouraged by visiting the home of every participant at the time of assessment. The significant association between participant compliance and maternal health value suggests Using cut-point of X191 counts/min (Hendelman et al, 2000). **Po0.001.…”
Section: Discussionmentioning
confidence: 98%
“…However, accelerometers are known to underestimate physical activity at specific activities, and this may lead to an underestimation of total energy expenditure. [22][23][24] As accelerometers can only provide information about acceleration, …”
Section: Discussionmentioning
confidence: 99%
“…14 The use of these cutoff points in field studies has been criticized. 23,25,26 It seems that when establishing cutoff points, the results are affected by the types of activities and the settings in which the calibration between activity counts and energy expenditure estimates is performed. 27 In this study, it is mostly ambulatory activity that is captured by the cut points used, meaning that the results have to be interpreted carefully.…”
Section: Validation Of the Ipaq In Adolescentsmentioning
confidence: 99%
“…One MET is equivalent to the energy expenditure for sitting quietly. Moderate activity is equal to between 3.0 and 6.0 METs (Hendelman, Miller, Baggett, Debold, & Freedson, 2000).…”
Section: Review Of the Literaturementioning
confidence: 99%